2021
DOI: 10.3390/metabo11120879
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Insights into Chemical Convergence in Xanthomonas perforans and Metabolic Changes Following Treatment with the Small Molecule Carvacrol

Abstract: Microbes are natural chemical factories and their metabolome comprise diverse arrays of chemicals. The genus Xanthomonas comprises some of the most important plant pathogens causing devastating yield losses globally and previous studies suggested that species in the genus are untapped chemical minefields. In this study, we applied an untargeted metabolomics approach to study the metabolome of a globally spread important xanthomonad, X. perforans. The pathogen is difficult to manage, but recent studies suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 162 publications
2
10
0
Order By: Relevance
“…Macrocarpal I compounds have no bacteriostatic activity against gram-negative bacteria and fungi, but have bacteriostatic activity against gram-positive bacteria ( Wei, 2015 ); PS[20:4(5Z,8Z,11Z,14Z)/14:0] is a glycerophospholipid that promotes the activation of glycerophospholipid metabolism and GPC pathway cycling ( Wu et al, 2021 ). Sarmentosin is an unsaturated γ-hydroxynitrile glucoside produced by plants and is often chelated by lepidopterans, sarmentosin was previously reported only in plant systems and reported this metabolite for the first time in microbial systems ( Jibrin et al, 2021 ). 2-isopropyl malic acid is an intermediate product of leucine biosynthesis ( Suzuki et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrocarpal I compounds have no bacteriostatic activity against gram-negative bacteria and fungi, but have bacteriostatic activity against gram-positive bacteria ( Wei, 2015 ); PS[20:4(5Z,8Z,11Z,14Z)/14:0] is a glycerophospholipid that promotes the activation of glycerophospholipid metabolism and GPC pathway cycling ( Wu et al, 2021 ). Sarmentosin is an unsaturated γ-hydroxynitrile glucoside produced by plants and is often chelated by lepidopterans, sarmentosin was previously reported only in plant systems and reported this metabolite for the first time in microbial systems ( Jibrin et al, 2021 ). 2-isopropyl malic acid is an intermediate product of leucine biosynthesis ( Suzuki et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite annotation was performed according to Level 2 of the Metabolomics Standards Initiative, as described previously [ 45 ]. The preliminary results of the one-way ANOVA after data normalization are shown in the Supplementary file (Figures S1a,b and S2a,b) .…”
Section: Resultsmentioning
confidence: 99%
“…The pathway analyses suggested that eugenol targets several pathways in X. perforans . The pathways that were significantly regulated by the putatively annotated metabolites in both untargeted search and when targeted against the Pseudomonas putida KT2440 are widely present in Gram-negative bacteria, including X. perforans [ 45 , 46 ]. At least 10 pathways and 12 pathways were significantly affected by the putatively annotated metabolites in the positive and negative ion phases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics can improve understanding of the interaction of bacterial spot pathogens and their hosts ( Strauss et al, 2012 ; Du et al, 2015 ; Shi and Panthee, 2020 ). Recently, known and novel metabolites from nonbacterial spot systems were reported in X. perforans ( Jibrin et al, 2021b ). Combining metabolomics and transcriptomics in studying isolates of the bacterial spot pathogens from Africa could provide additional insights into the diversity of molecules that are important in host–pathogen or other ecological interactions and their pathways and expressed genes.…”
Section: Conclusion and Recommendations For Future Studiesmentioning
confidence: 99%